Fundamental Mechanisms of Reversible Dehydrogenation of Formate on N-Doped Graphene-Supported Pd Nanoparticles - Shin, Dong Yun; Kim, Min-Su; Kwon, Jeong An; Shin, Yeon-Jeong; Yoon, Chang Won; Lim, Dong-Hee (American Chemical Society, 2019)
Reversible formate (HCOO-) dehydrogenation and bicarbonate (HCO3-) hydrogenation would be desirable for the utilization and storage of hydrogen (H-2) as an effective energy carrier. Carbon-supported Pd-based nanoparticles demonstrated enormous competitive advantages for these reactions. However, the fundamental mechanisms underlying these reversible reactions have not yet been elucidated. Herein, we report the reaction pathways for reversible reactions on a Pd-based catalyst using density functional theory (DFT) calculations and propose key factors for improving the reaction efficiency. As the first essential step, the difficulty in the conventional DFT modeling, that is simulation of an anion environment caused by HCOO-, was overcome by designing two-sided Pd-12 nanoclusters supported on graphene (Pd12NC-G) with extra electrons. Using Pd12NC-G, we demonstrated that the key factor determining the potential limiting steps for the reversible reaction was desorption of hydrogen in HCOO-dehydrogenation (1.24 eV) and HCO3- hydrogenation (1.49 eV). The key factor was the same in Pd12NC-N(1)G, Pd12NC-N(2)G, and Pd12NC-N(3)G (where N-1, N-2, and N-3 represent the number of N atoms doped on carbon). Among these, the Pd12NC-N(2)G model with the appropriate amount of nitrogen doping showed optimal hydrogen adsorption strength corresponding to the smallest d-band center and spin density values, resulting in the lowest energy barriers for HCOO- dehydrogenation (0.76 eV) and HCO3- hydrogenation (0.96 eV). Based on harmonization between electronic and geometrical properties, we demonstrated that the appropriate level of nitrogen doping can provide the optimal balance between the magnitude of reactivity and the number of sites for improving the efficiency of the reversible reactions.
Keywords: FORMIC-ACID DECOMPOSITION; OXYGEN REDUCTION REACTION; HYDROGEN STORAGE; CATALYSTS; CARBON; PALLADIUM; DFT; ELECTROCATALYST; 1ST-PRINCIPLES; ADSORPTION